PENGEMBANGAN PRODUK TAHU WALIK TANPA DAGING MELALUI STRATEGI PEMASARAN DIGITAL DAN SISTEM PRE-ORDER - Farhan As Sidiq; Jawarno; Yulia Widia Pengestika; Anita Indah; Unna Ria Safitri (KRIDA CENDEKIA, 2025)
This research examines the development of traditional culinary products, specifically tahu walik without meat, as a form of entrepreneurial innovation among students by utilizing a pre-order system and digital marketing. This study uses a qualitative descriptive approach with a case study method on a tahu walik business run by a group of students with an initial capital of IDR 500,000. Data were collected through participatory observation, unstructured interviews, documentation, and business activity records during the development and implementation period.The results show that meatless tahu walik was successfully developed as an innovative product that combines traditional flavors with modern sustainability-based concepts. The decision to remove meat from the product composition was based on three main considerations: production cost efficiency, targeting the vegetarian market segment, and supporting environmentally friendly concepts. The product was developed in several flavor variants, such as balado, sweet corn, mayonnaise, and original, to meet diverse consumer preferences.Digital marketing strategies through WhatsApp and Instagram with a pre-order system proved effective in reaching consumers with minimal costs. This approach allows for interactive personal communication, reduces the risk of overproduction, ensures better cash flow, and builds customer loyalty through an exclusive ordering system. The pre-order system also provides flexibility to customize products according to consumer demand. Pricing strategies show good adaptability to dynamic market conditions. The initial phase used a premium price of IDR 13,000 to measure product value perception, then adjusted to IDR 10,000 when participating in an expo as a market penetration strategy. This pricing flexibility reflects the ability to read market dynamics and make strategic adjustments. Financial analysis shows good profit potential with an efficient cost structure without using meat, allowing for optimal profit margins. Break-even analysis shows that the break-even point can be achieved in a relatively short time with the support of a pre-order system that minimizes waste.This research proves that traditional food product innovation can be developed with limited capital by integrating traditional values with a business approach responsive to modern market dynamics. The success of the tahu walik business lies not only in the uniqueness of the physical product but also in the ability to integrate cost-effective digital marketing, pricing strategy flexibility, and operational efficiency. This business model provides a valuable lesson for entrepreneurs looking to innovate in the culinary industry.